Structural and morphological characterization of Pb1-xBaxTiO3 thin films prepared by chemical route: An investigation of phase transition - Pontes, Fenelon Martinho Lima [UNESP]; Galhiane, Mario Sergio [UNESP]; Santos, L. S. [UNESP]; Rissato, R. S. [UNESP]; Pontes, D. S. L. [UNESP]; Longo, Elson [UNESP]; Leite, E. R.; Pizani, P. S.; Chiquito, A. J.; Machado, M. A. C. (Elsevier B.V. Sa, 2008)
Detailed room temperature micro-Raman scattering, X-ray diffraction, atomic force microscopy and specular reflectance infrared Fourier transform spectroscopy studies were carried out on soft chemical by processed Pb1-xBaxTiO3 thin films. The micro-Raman spectra pointed the existence of a stable tetragonal ferroelectric phase in the entire composition range (0 < x <= 1). The infrared reflectance spectra showed that the frequency of several peaks decreases as the Ba2+ concentration increases. These features are correlated to a decrease in the tetragonal distortion of the TiO6 octahedra as the Ba2+ concentration increases. Furthermore, as x increases from 0.70 to 1.0, the Raman spectrum shows an evolution towards the well-known Raman spectrum of the tetragonal BaTiO3. Therefore, we demonstrated that the combination of solid solution PbTiO3-BaTiO3 with a grain size in the order of 30-40 nm supports the tetragonal ferroelectric phase at room temperature. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: thin films; chemical synthesis; microstructure; phase transitions